Competitive Equilibria in Markets with a Continuum of Traders and Incomplete Preferences - Schmeidler, David (Econometrica, 1969)
Abstract : It is shown that a market with a continuum of traders possesses a competitive equilibrium even when the preferences are not complete. This generalizes further a result of Aumann, ('Econometrica'; 32: 39-50 (1964); 34: 1-17(1966)) who showed that the convexity assumption may be dispensed within the presence of a continuum of traders. The proof is inspired by the Arrow-Debreu ('Econometrica; 22: 265-290(1954)) proof for the finite case. (Author)